Family Support as Caregivers for Independent Management of Hypertension Patients: Literature Review - Kartika Setia Purdani; Muhammad Ridwan; Bunga Yusnanda; Yunisah Fitri; Twy Kurmiantin; Lutfi Nur Amalia (INDOGENIUS, 2026)
Background & Objective: Hypertension is a significant global health problem, and family support as caregivers can play a role in the self-management of hypertensive patients. This review aims to evaluate the effectiveness of family support in helping hypertensive patients. Method: This study used a literature review approach with descriptive analysis. Data were obtained from scientific articles published between 2022 and 2024 through the Google Scholar and PubMed databases. A total of 15 relevant articles were selected based on inclusion criteria. Result: Family support has been shown to be effective in improving patient compliance with hypertension treatment, controlling blood pressure, and improving quality of life. Non-pharmacological interventions such as family education and relaxation therapy have shown significant positive effects. Conclusion: Family support is an important factor in managing hypertension and should be integrated into health programs to improve hypertension management outcomes in the community.